A criterion for identifying a mixed-mode I/II hydraulic fracture crossing a natural fracture in the subsurface. Issue 6 (November 2020) - Zeng, Yijin; Cheng, Wan; Zhang, Xu; Xiao, Bo
Hydraulic fracturing has been proven to be an effective technique for stimulating petroleum reservoirs. During the hydraulic fracturing process, the effects of the natural fracture, perforation orientation, stress reorientation, etc. lead to the production of a non-planar, mixed-mode I/II hydraulic fracture. In this paper, a criterion for a mixed-mode I/II hydraulic fracture crossing a natural fracture was first proposed based on the stress field around the hydraulic and natural fractures. When the compound degree (KII /KI ) approaches zero, this criterion can be simplified to identify a pure mode I hydraulic fracture crossing a natural fracture. A series of true triaxial fracturing tests were conducted to investigate the influences of natural fracture occurrence and in situ stress on hydraulic fracture propagation. These experimental results agree with the predictions of the proposed criterion.